PEMANFAATAN ANALISIS JABATAN DALAM AKTIVITAS MANAJEMEN SUMBERDAYA MANUSIA DI KANTOR PERPUSTAKAAN KOTA MALANG - Lestari Eko Wahyudi (REFORMASI, 2015)
The issue of overlapping duties and functions, overlapping workloads, and subjectivity redistribution employees are human resource management issues are complicated and difficult to solve especially in public sector organizations. Job analysis and workload analysis is a tool that can help to provide a relevant consideration employment policy formulation, management, institutional and supervision. This researc has the objective to describe and analyze the implementation of the results of job analysis and workload analysis on human resource management activities in the Office of the Public Library Malang to improve employee performance. This research uses descriptive method with qualitative approach. The findings in this study is the lack of utilization of the results of job analysis and the workload on the organization of the public sector, where the condition is affected by the limitations of the budget allocation, the commitment of top managers, the dominance of interests, and negative perceptions.